Chemistry of Substituted Thiazinanes and Their Derivatives - Hassan, Alaa A. (Molecules, 2020)
Thiazinanes and its isomeric forms represent one of the most important heterocyclic compounds, and their derivatives represented a highly potent drug in disease treatment such as, 1,1-dioxido-1,2-thiazinan-1,6-naphthyridine, which has been shown to have anti-HIV activity by a mechanism that should work as anti-AIDS treatment, while (Z)-methyl 3-(naphthalen-1-ylimino)- 2-thia-4-azaspiro[5 5]undecane-4-carbodithioate showed analgesic activity, cephradine was used as antibiotic and chlormezanone was utilized as anticoagulants. All publications were interested in the chemistry of thiazine (partially or fully unsaturated heterocyclic six-membered ring containing nitrogen and sulfur), but no one was dealing with thiazinane itself which encouraged us to shed new light on these interesting heterocycles. This review was focused on the synthetic approaches of thiazinane derivatives and their chemical reactivity.